Action of a Pyrimido-pyrimidine Compound on Platelet Behaviour in Vitro. Issue 5655 (24th May 1969) - Forbes, C. D.; McNicol, G. P.; Douglas, A. S.
Abstract : A pyrimido-pyrimidine compound (RA433) was found in vitro to be a significantly more potent inhibitor of platelet behaviour than the previously available pyrimido-pyrimidine compound RA8—dipyridamole. In a turbidimetric system RA433 inhibits platelet aggregation induced by adenosine diphosphate, collagen, and noradrenaline; further, in a glass-bead-column technique it is a powerful inhiitor of platelet adhesiveness.